2006
DOI: 10.4049/jimmunol.177.9.6108
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Selective Priming of FcαR on Eosinophils by Corticosteroids

Abstract: Preactivation or priming of eosinophils by (proinflammatory) cytokines is important in the pathogenesis of allergic diseases. Several priming-dependent eosinophil responses, such as migration and adhesion, are reduced by treatment with corticosteroids. Many inhibitory effects of corticosteroids are mediated by the glucocorticoid receptor via genomic mechanisms, which are evident only after prolonged interaction (>30 min). However, also faster actions of corticosteroids have been identified, which occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Cytokine signaling has been shown to enhance ligand binding to the IgA and IgG Fc receptors [40], [41]. The signaling pathways that mediate this effect have been identified [42], [43], but the changes to the extracellular domains to allow for enhanced ligand binding remain unknown. Interesting for CEACAM1 [44], interactions between GXXXG transmembrane motifs appears to stabilize cis-dimers in the inactive form.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine signaling has been shown to enhance ligand binding to the IgA and IgG Fc receptors [40], [41]. The signaling pathways that mediate this effect have been identified [42], [43], but the changes to the extracellular domains to allow for enhanced ligand binding remain unknown. Interesting for CEACAM1 [44], interactions between GXXXG transmembrane motifs appears to stabilize cis-dimers in the inactive form.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has demonstrated that GCS are able to induce proinflammatory responses in these cells [20][21][22][23][24][25][26]. We tested the hypothesis that GCS affect TNF-a-induced synthesis and secretion of pro-and anti-inflammatory cytokines by neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the strong capacity of GCS to inhibit inflammation, inhibition of neutrophil-driven inflammation seems to be less effective [19]. Other studies have shown that GCSs elicit proinflammatory effects on granulocytes, such as increased interleukin (IL)-1 receptor (IL-1R) type I expression on human neutrophils [20], prolonged neutrophil survival in vitro [21,22], leukocytosis in vivo [23], p38 activation in neutrophils and eosinophils [24,25], increased immunoglobulin A binding by eosinophils [25], and increased secretion of lysosomal enzymes by neutrophils [26]. Because not only proinflammatory, but also anti-inflammatory, mediators are controlled by the transcription factor NF-kB, GCSs would be expected to affect the expression of anti-inflammatory response as well, which is not often assessed.…”
mentioning
confidence: 99%
“…The supernatants were analyzed in an anti-TNFα ELISA as described [ 31 , 42 ]. Briefly, microtiter plates were coated with mouse anti-human TNFα capture ab (2 μg/ml) (MAB610/clone 28401; R&D Systems, USA) overnight in a humid chamber.…”
Section: Methodsmentioning
confidence: 99%